Optimal mode for delivery of seasonal malaria chemoprevention in Ouelessebougou, Mali: A cluster randomized trial. - Amadou Barry; Djibrilla Issiaka; Tiangoua Traore; Almahamoudou Mahamar; Boubacar Diarra; Issaka Sagara; Diakalia Kone; Ogobara K Doumbo; Patrick Duffy; Michal Fried; Alassane Dicko (PLoS ONE, 2018)
Seasonal malaria chemoprevention (SMC), the administration of complete therapeutic courses of antimalarials to children aged 3-59 months during the malaria transmission season, is a new strategy recommended by the World Health Organization (WHO) for malaria control in Sahelian countries such as Mali with seasonal transmission. The strategy is a highly cost-effective approach to reduce malaria burden in these areas. Despite the substantial benefits of SMC on malaria infection and disease, the optimal approach to deliver SMC remains to be determined. While fixed-point delivery (FPD) and non-directly observed treatment (NDOT) by community health workers are logistically attractive, these need to be evaluated and compared to other modes of delivery for maximal coverage.To determine the optimal mode fixed-point (FPD) vs door-to-door delivery (DDD); directly observed treatment (DOT) vs. non- directly observed treatment (NDOT)), 31 villages in four health sub-districts were randomized to receive three rounds of SMC with Sulfadoxine-pyrimethamine plus Amodiaquine (SP+AQ) at monthly intervals using one of the following methods: FPD+DOT; FPD+NDOT; DDD+DOT; DDD+NDOT. The primary endpoint was SMC coverage assessed by cross-sectional survey of 2,035 children at the end of intervention period.Coverage defined as the proportion of children who received all three days of SMC treatment during the three monthly rounds based information collected by interview (primary endpoint) was significantly higher in children who received SMC using DDD 74% (95% CI 69% - 80%) compared to FPD 60% (95% CI 50% - 70%); p = 0.009. It was similar in children who received SMC using DOT or NDOT 65%, (95% CI 55% - 76%) versus 68% (95% CI 57% - 79%); p = 0.72.In summary, door-to-door delivery of SMC provides better coverage than FPD. Directly observed therapy, which requires more time and resources, did not improve coverage with SMC.ClinicalTrials.gov NCT02646410.